Approximate reasoning on a DNA-chip - Ray, Kumar S.; Chatterjee, Piyali (International journal of intelligent computing and cybernetics, 2010)
Purpose - The purpose of this paper is to propose an alternative approach to approximate reasoning by DNA computing, thereby adding a new dimension to the existing approximate reasoning method by bringing it down to nanoscale computing. The logical aspect of approximate reasoning is replaced by DNA chemistry.Design methodology approach - To achieve this goal, first the synthetic DNA sequence fuzzified by quantum dot, which is a recent advancement of nanotechnology. Thus with the help of fuzzy DNA, which holds the vague concept of human reasoning, the basic method of approximate reasoning on a DNA chip is realized. This approach avoids the tedious choice of a suitable implication operator (for a particular application) necessary for existing approximate reasoning based on fuzzy logic. The inferred consequences obtained from DNA computing-based approximate reasoning is ultimately hybridized with appropriate complementary sequence probed on a DNA-chip to confirm the result of inference.Findings - The present approach is suitable for reasoning under vague and uncertain environment and does not require any subject choice of any individual expert, which is essential for existing approximate reasoning method.Originality value - This new tool for approximate reasoning based on DNA computing is applicable to several problems of science and engineering; namely pattern classification, control theory, weather forecasting, atmospheric science, etc.